Chemical preparation of activated carbon from Acacia erioloba seed pods using H2SO4 as impregnating agent for water treatment: An environmentally benevolent approach. (10th November 2019) - Rahman, Ateeq; Hango, Heita James; Daniel, Likius Shipwiisho; Uahengo, Veikko; Jaime, Sirunda Johannes; Bhaskaruni, Sandeep V.H.S.; Jonnalagadda, Sreekantha Babu
Abstract: The aim of this research study was to prepare activated carbon from Acacia erioloba ( A. erioloba ) seedpods and evaluate its application for water treatment. The prepared activated carbon was characterized by using different analytical techniques including; Fourier-transform infrared spectroscopy, scanning electron microscopy, Brunauer–Emmett–Teller, x-ray diffraction, transmission electron microscopy, energy dispersive x-ray, iodine number, and methylene blue index to determine the adsorption properties of the prepared activated carbon. Methylene blue dye was used in this study to evaluate the adsorption capacity of the prepared activated carbon. From the results, it was found that the adsorption of methylene blue by activated carbon favored Freundlich adsorption isotherm, indicating that methylene blue particles were adsorbed on heterogeneous surfaces. Iodine number was found to be in the range 528–638 mg/g. Brunauer–Emmett–Teller surface area was found to be in the range 121–372 m 2 /g. Pore volumes between 0.0239 and 0.0483 cm 3 /g and pore sizes in the range 21–45 Å were found. The prepared activated carbon was also evaluated for its applicability in water treatment and it was found to have adsorbed total dissolved solids from water by 36–43%. However, the activated carbon's surface contained metals such as iron, which desorbed from its surface into the treated water suggesting that A. erioloba -seed-pod-based- activated carbon may not be ideal for water treatment with high iron concentration. Therefore, from all the results presented in this study, activated carbon from A. erioloba seed pods showed adsorption properties for its application in water treatment. Indeed, activated carbons, which are applicable for water treatment, can be prepared from readily available and cheap raw material with possible recycling of activating agents and regeneration of spent activated carbon hence, the concept of Cleaner Production. Thus, this research study will be of interest to water treatment utilities, especially those in water stressed countries such as Namibia. Graphical abstract: Image 1 Highlights: This work highlights about the treatment of different waste waters with activated carbon prepared from acacia pods. Activated carbon from acacia pods is prepared in under different conditions, and applied for waste water treatment. Activated carbon is characterized by FT-IR, XRD, SEM, TEM.